A comparison of organ-tissue level body composition between college-age male athletes and nonathletes - Midorikawa, T.; Sekiguchi, O.; Beekley, M. D.; Bemben, M. G.; Abe, T. (International Journal of Sports Medicine, 2007)
The purpose of this study was to compare the characteristics of skeletal muscle (SM) mass and internal organ (liver and kidney) mass in resistance and/or high intensity trained collegiate athletes with nonathletes, and to examine the relationships between fat-free mass (FFM) and its major components of SM, liver mass, and kidney mass. Fifteen athletes and seventeen nonathletes volunteered for the study. FFM was measured by two-compartment densitometry. Contiguous magnetic resonance imaging was used to obtain images from the first cervical vertebrae to the ankle joint (no inter-slice gap) for each subject, and SM, liver and kidney cross-sectional areas and organ-tissue volumes were determined. Organ-tissue volumes (cm3) were converted to mass (kg) by multiplying the volumes by the assumed constant density of the tissues. On average, athletes had greater FFM (69.1 kg) than the nonathletes (52.6 kg). SM, liver, and kidney masses in athletes (33.0 kg, 1.84 kg and 0.39 kg, respectively) were higher compared with nonathletes (23.5 kg, 1.39 kg and 0.31 kg, respectively). When the various determinants of FFM were expressed as ratios, it was determined that the ratio of SM mass to FFM was higher in athletes (47.7 %) than nonathletes (44.7 %), and the ratios of liver and kidney to FFM were similar for the two groups (2.6 % and 0.6 %, respectively, for athletes; and 2.7 % and 0.6 %, respectively, for nonathletes). A strong correlation between FFM and SM mass was observed in athletes and nonathletes and the slopes of these regression lines were almost identical and parallel. FFM was also significantly correlated with liver and kidney mass for both athletes and nonathletes. This study suggests that SM, liver, and kidney masses are increased by FFM accumulation in resistance and/or high intensity trained athletes.